71. Repetitive Transcranial Magnetic Stimulation (rTMS) applied with H-coil in Alzheimer's disease: A placebo-controlled, double-blind, pilot study. Issue 4 (April 2016) - Coppi, E.; Ferrari, L.; Nuara, A.; Chieffo, R.; Houdayer, E.; Ambrosi, A.; Bernasconi, M.P.; Falautano, M.; Zangen, A.; Comi, G.; Magnani, G.; Leocani, L.
Abstract : Focal rTMS in Alzheimer's disease (AD) revealed cognitive benefits. H-coil can depolarize deeper and wider structures compared with focal coils, thus targeting widespread networks involved in neurodegenerative disorders. We aimed to evaluate H-coil rTMS safety and efficacy in AD. Thirty AD subjects (70.21 ± 8.66 y.o.), randomized in real or sham groups, underwent 16 rTMS sessions (3 weekly for 4 weeks, 1 weekly for other 4 weeks), over fronto-parieto-temporal lobes at 10 Hz. Neuropsychological assessment was performed at baseline, after 4 weeks (4w), at the end of treatment (8w). Primary outcome was an improvement in Alzheimer's disease scale-cognitive (ADAS-cog). No serious side effects were reported. Four subjects were excluded (1 acute myocardial infarction in the sham group, 1 misdiagnosis, 2 missing data), thus statistical analysis included 26 subjects. At 4w, percent ADAS-cog improvement from baseline (4 w%) was greater in the real compared with the sham group ( p = 0.042). The relationship between baseline ADAS-cog and 4 w% differed between the two groups ( p = 0.009), with higher improvement for less cognitively impaired subjects at baseline only in the real. These findings suggest that H-coil may be safe and effective in AD and that deep rTMS may better impact the course of the disease when administered at earlier stages.